From Intent to Action: An Iterative Engineering Process | De l'intention à la maturité : une ingénierie itérative - Patrice Mouton; Jacques Rodet; Sylvain Vacaresse (The Canadian Network for Innovation in Education (CNIE), 2015)
Quite by chance, and over the course of a few haphazard meetings, a Master's degree in E-learning Design gradually developed in a Faculty of Economics. Its original and evolving design was the result of an iterative process carried out, not by a single Instructional Designer (ID), but by a full ID team. Over the last 10 years it has been successfully delivered by focusing on its strengths: the tutorial system, synchronous-mode online learning, collaborative work, and the supervision of professional projects. However, its success has led to new issues such as larger groups of enrolled students, program diversification, and internationalization.